MEMBACA PELUANG MERAKIT “UANG” DARI HOBI AQUASCAPE - Hariyatno, Hariyatno; Isanawikrama, Isanawikrama; Wimpertiwi, Dotty; Kurniawan, Yohanes Jhony (Universitas Bunda Mulia, 2018)
ABSTRACT The purpose of this study is to find out what are the advantages derived from the art of aquascape and any business opportunities that arise as a result of this hobby, lately many people began to love the art of aquarium-made beauty that is decorated with neat and unique decoration, if akita observe products that produce a miniature underwater ecosystem is so beautiful and cool eye-catching that is better known by the name of aquascape, along with the many requests for aquascape art is now beginning emerging aquarium merchants that also provide services aquascape manufacture and maintenance, together with the perminaan equipment good accessories aquarium machines, iron or wood shelves, flora and fauna continue to increase, because to make an aquascape product in need of adequate equipment and equipment to support maximum results, the results of this study took samples of aquascape aquascape, aquascape craftsmen and store access stores oris ornamental fish that exist in Bogor. Data analysis in this research using full costing method to determine selling price. The results showed that aquascape is a hobby that started in like someone, become a promising business field, it turns out the advantage of making aquascape craftsmen obtain 18.30% for aquascape model 1 and 31.24% for aquascape model 2 has not profit from the difference in raw materials in use reach 10%, from the cost incurred where the profit obtained depends on the uniqueness and beauty. so many people who had just a hobby to make as a land of business.Key Words: Aquascape, Hobby, Money, Reading Opportunity